2019
DOI: 10.1159/000499906
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Severe Generalized Junctional Epidermolysis Bullosa by Systemic Treatment with Gentamicin

Abstract: Severe generalized junctional epidermolysis bullosa (JEB), a lethal genodermatosis, is mainly caused by premature termination codons (PTCs) in one of the three genes encoding the anchoring protein laminin-332. Only symptomatic treatment has been established; overcoming PTCs by aminoglycosides may represent an interesting alternative. This retrospective study aimed at assessing for the first time the clinical effects of systemic gentamicin application in infants with severe generalized JEB. Five patients, homoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…only, leading to improved skin stability and quality-of-life (QoL) in 4/5 patients. However, in this study it did not postpone lethality [61]. Currently, two trials involving gentamicin treatment are running (NCT04140786, NCT03526159), aiming to increase laminin-332 and C7 expression in order to induce the generation of new hemidesmosomes and anchoring fibrils, respectively, monitored by immune-and electron microscopy of skin biopsies.…”
Section: Summary Of Publications On Recent (R)ct-trials and Current Cmentioning
confidence: 80%
“…only, leading to improved skin stability and quality-of-life (QoL) in 4/5 patients. However, in this study it did not postpone lethality [61]. Currently, two trials involving gentamicin treatment are running (NCT04140786, NCT03526159), aiming to increase laminin-332 and C7 expression in order to induce the generation of new hemidesmosomes and anchoring fibrils, respectively, monitored by immune-and electron microscopy of skin biopsies.…”
Section: Summary Of Publications On Recent (R)ct-trials and Current Cmentioning
confidence: 80%
“…In fact, the outcome of these studies might pose the basis for a potential use of Hologene 5 also in some selected severe forms of JEB, which are characterized by undetectable expression of laminin 332 ( Kopp et al, 2005 ; Hammersen et al, 2016 ). In this respect, it has been shown that gentamicin can induce read-through of nonsense mutations and partially restore the expression of laminin 332 in patients with double null mutations in LAMB3 alleles, without triggering any immune reaction ( Hammersen et al, 2019 ; Kwong et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial impact on skin fragility was noted in four out of five patients, although the drug failed to prevent premature death. Early demise due to failure to thrive, airway obstruction and sepsis within the first 2 years of life is prototypic for this severe EB subtype [ 113 ]. Prospective studies to assess the safety and efficacy of intravenous gentamicin are ongoing (NCT03526159, NCT03392909, NCT04140786).…”
Section: Premature Termination Codon (Ptc) Readthrough Therapiesmentioning
confidence: 99%